2016
DOI: 10.1371/journal.pone.0147398
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of Beach Morning Glory (Ipomoea imperati) under Salinity and Its Comparative Analysis with Sweetpotato

Abstract: The response and adaption to salt remains poorly understood for beach morning glory [Ipomoea imperati (Vahl) Griseb], one of a few relatives of sweetpotato, known to thrive under salty and extreme drought conditions. In order to understand the genetic mechanisms underlying salt tolerance of a Convolvulaceae member, a genome-wide transcriptome study was carried out in beach morning glory by 454 pyrosequencing. A total of 286,584 filtered reads from both salt stressed and unstressed (control) root and shoot tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 73 publications
(99 reference statements)
1
7
0
Order By: Relevance
“…FAD2 genes exhibited higher expression in the qRT-PCR validation experiment at 140 DAF. Such inconsistency in the expression level of FATB and FAD2 genes could be due to primers’ specificity and qRT-PCR reaction conditions during the experimental validation analysis [75].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…FAD2 genes exhibited higher expression in the qRT-PCR validation experiment at 140 DAF. Such inconsistency in the expression level of FATB and FAD2 genes could be due to primers’ specificity and qRT-PCR reaction conditions during the experimental validation analysis [75].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…14) and a somatic hybrid between the two species, finding genes that are differentially regulated in the I. batatas parent compared to either I. triloba or the hybrid, which are more drought tolerant. Other de novo transcriptome approaches have been reported for hexaploid Ipomoea trifida and Ipomoea imperati for drought and salt stress, respectively (Peng et al., ; Solis, Baisakh, Brandt, Villordon, & Bonte, ). In this study, global gene expression patterns in leaf tissue of two varieties of I. batatas , Beauregard, and Tanzania, during PEG‐simulated drought stress were characterized with RNA‐Sequencing (RNA‐Seq); diploid I. trifida , which is closely related to I. batatas and is a putative progenitor species (Austin, ; Kobayashi, ), was used as the reference genome sequence (http://sweetpotato.plantbiology.msu.edu/gt4sp_download.shtml).…”
Section: Introductionmentioning
confidence: 99%
“…Although salt‐tolerant plants usually have a better ability to exclude sodium to avoid toxic sodium concentrations in the cell (Bose, Rodrigo‐Moreno, & Shabala, ; Kosová, Prášil, & Vítámvás, ), Ca 2+ elevation and proper ROS regulation with higher antioxidant capacity are believed to be key components in the salinity tolerance response in plants (Bose et al, ; Kader & Lindberg, ). Recently Solis, Baisakh, Brandt, Villordon, and La Bonte () found that genes encoding calcineurin B‐like (CBL)‐interacting protein kinases (CIPKs) were induced in a halophyte relative of sweet potato, suggesting a role of a Ca 2+ signalling pathway in salinity tolerance. The crosstalk of ROS production with other signalling molecules, such as ABA, JA, and their downstream signalling components, has been shown to play an essential role in salinity tolerance response (Fahad et al, ; Kurusu et al, ; Zhang, Smith, Harberd, & Jiang, ).…”
Section: Adaptive Mechanisms and Signalling During Salt Exposurementioning
confidence: 99%